2020
DOI: 10.1097/brs.0000000000003439
|View full text |Cite
|
Sign up to set email alerts
|

The NuVasive MAGEC Rod Urgent Field Safety Notice Concerning Locking Pin Fracture

Abstract: Study Design. Analysis of explanted MAGnetic Expansion Control (MAGEC) growing rods. Objective. The aim of this study was to quantify the rate of locking pin breakage in explanted MAGEC rods and compare with the manufacturer's data. Summary of Background Data. On June 25, 2019, NuVasive released an Urgent Field Safety Notice stating that MAGEC rods manufactured before March 26, 2015 had a higher than expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…drive pin or lead screw fractures), and is hypothesised to be caused by high-frictional forces inside the actuator [6,7]. While newer versions of the MCGR have been developed, mechanical complications remain prevalent [8]. The re-operations necessary to correct these complications are a serious burden for the patient and increases treatment cost dramatically, potentially making MCGR treatment less cost-effective than previously described, as calculations were based only on a relatively short follow-up [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…drive pin or lead screw fractures), and is hypothesised to be caused by high-frictional forces inside the actuator [6,7]. While newer versions of the MCGR have been developed, mechanical complications remain prevalent [8]. The re-operations necessary to correct these complications are a serious burden for the patient and increases treatment cost dramatically, potentially making MCGR treatment less cost-effective than previously described, as calculations were based only on a relatively short follow-up [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to perform an equitable comparison between the 2 rod design iterations, only MAGEC 1.3 implants with a time to removal less than 34 months (maximum time to removal of a MAGEC X implant recorded at our retrieval centre) were included. Time to removal has been found to significantly influence retrieval findings, including wear rate, 10 force generated by the implant, 11 pin fracture, 12 and implant functionality. 13 Excluding implants with longer follow-up led to an overall relatively high implant-related reason for removal (in 13/20 patients).…”
Section: Discussionmentioning
confidence: 99%
“…A previous retrieval study reported evidence of locking pin fractures in 62 of 105 (59%) and 6 of 29 (21%) of rods collected at their center that had been manufactured before and after this date, respectively. 12 This study also indicated that the earlier design was grade 440 stainless steel, which changed to 465 stainless steel.…”
mentioning
confidence: 82%